Comparison effect of lavender oil inhalation and tea on sleep quality, fatigue, and pain in hemodialysis patients: A randomized clinical trial - Vahideh Aghamohammadi (Nursing Practice Today, 2025)
Background & Aim: The pain of needle insertion in arteriovenous fistula, fatigue, and sleep disturbances are common problems in hemodialysis patients. Using lavender products can help reduce these problems. This study aimed to compare the effects of lavender aromatherapy and lavender tea consumption on reducing pain and fatigue, as well as improving sleep quality in hemodialysis patients. Methods & Materials: This study is an open-label trial conducted at the Dialysis Center at Tabriz University of Medical Science from May to December 2022. Random allocation was done by randomizing the moved blocks. hemodialysis patients were allocated to one of the three study groups: control (n=30), lavender inhalation (n=30), and lavender tea (n=30). At the baseline and the end of the study, Participants' sleep quality with PSQI, fatigue with FSS, and pain of needle insertion in arteriovenous fistula with Vas scale were assessed. The data analysis was performed using SPSS software The Analysis of covariance (ANCOVA) test was used to compare the mean of variables between the study groups. Results: A comparison of the follow-up scores between 3 groups shows that participants in the lavender tea group and lavender aromatherapy group had a lower score of total score of PSQI (P<0.001), fatigue (P<0.001), and pain(P<0.001) following the intervention compared to the control group. Also, there was no statistically significant difference between the lavender tea group and the lavender aromatherapy group in terms of sleep quality scores (P=0.428), fatigue (P=0.570), and pain (P=0.997). Conclusion: The findings of this study showed that lavender can be useful in improving the problems of dialysis patients, such as sleep quality, fatigue, and pain caused by needle insertion.